Pengaruh Kecepatan Pengadukan Terhadap Kinetika Reaksi Pembentukan Hidroksiapatit (HAp) Dari Precipitated Calcium Carbonate (PCC) Cangkang Telur Itik Melalui Proses Presipitasi - Bintoro Bintoro; Yelmida Azis; Fajril Akbar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Hydroxyapatite (Ca10(PO4)6(OH)2) is a calcium phosphate compound that has been widely used as a bone implant material because its chemical composition is identical with natural bone. The purposes of this research are synthesis, characterization and study of kinetics of hydroxyapatite formation reaction with PCC (Precipitated Calcium Carbonate) base material of duck eggshell using precipitation method. In this study the samples were taken every 10 minutes as much as 10 mL for 1 hour of stirring, continued stirring up to 24 hours with variation of stirring speed (100; 150; 200; 250; 300 rpm) and ageing for 24 hours. The analysis of Ca concentration in the filtrate was done using the complexometry method. Hydroxyapatite is characterized by XRD. The crystalline structure and the calcium phosphate group in the sample indicate the hydroxyapatite compound. Kinetic synthesis reactions follow the second order equation with the value of reaction rate constant obtained by 0,6277, 0,7284, 0,7668, 0,5674, 0,6285 minutes-1. Keywords: Hydroxyapatite, kinetics reaction, PCC, duck’s eggshell, precipitation, second order